Manajemen Klinis Tuberkulosis Paru Resistan Obat pada Lansia: Studi Kasus di Instalasi Rawat Inap RSUD Prof. Dr. Aloei Saboe - Papeo, Dizky R.; Aulia, Tita Arikah; Husain, Siti Dinarti; Selviana, Selviana; Pangaribuan, Jhuandaniel Piator; Anwar, Alvionita B. (Lontara Journal of Health Science and Technology, 2026)
Drug-resistant pulmonary tuberculosis (DR-TB) is a challenging form of TB characterized by resistance to at least rifampicin and isoniazid, requiring the use of complex second-line therapies. This condition is often accompanied by complications that further aggravate the clinical course. The aim of this study was to evaluate the management of DR-TB with complications. This retrospective case study was based on the medical record of a 63-year-old female patient with a history of TB in 2020 who was diagnosed with relapsed DR-TB complicated by hypertension, anemia, and insomnia. The diagnosis was confirmed through a rapid molecular test showing a positive result for Mycobacterium tuberculosis with rifampicin resistance. Initial management included the administration of second-line antibiotics, blood transfusion to address anemia, and supportive care for accompanying symptoms. Following two consecutive positive results, the patient commenced second-line anti-tuberculosis (ATT) therapy according to MDR-TB treatment standards. Evaluation revealed improvement in hemoglobin levels after transfusion, although shortness of breath persisted and required further monitoring. In conclusion, the management of DR-TB with complications requires a multidisciplinary approach tailored to the patient’s clinical condition